ANALISIS PENGARUH PERSEPSI HARGA, KUALITAS PRODUK DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN PAKAN IKAN DENGAN CITRA MEREK SEBAGAI VARIABEL INTERVENING (STUDI PADA PT. CENTRAL PROTEINA PRIMA CABANG TEGAL) - Nisrina Cahya Kamila; Imroatul Khasanah (Faculty of Economics and Business Diponegoro University, 2022)
Along with the development of today's increasingly rapid and more and more competition, especially in the fields of business, industry and trade. This makes the competition between companies increasingly fierce. Therefore, companies must compete with each other and compete to provide the best for consumers. The company must have a strategy to analyze competitors. Because analyzing competition is very important to find out the extent to which competitors' businesses make changes and developments in their business, it is expected to be able to encourage companies to improve superior products and increase creativity and innovation in products offered to consumers. aims to analyze the effect of price perception, product quality, promotion on purchasing decisions of fish feed with brand image as an intervening variable (Study at PT. Central Proteina Prima Cab. Tegal.) The population used in this study were consumers who had purchased fish feed at C.P. Prima Cab. Tegal. the number of samples used in this study were 120 respondents. The data method used in this research is a questionnaire. The data obtained were then processed and analyzed using the Structural Equation Modeling (SEM) analysis technique with the AMOS 24. analysis tool. Based on the results of this study, it was found that price perception has a positive and significant effect on brand image. product quality has a significant positive effect on brand image, promotion has a positive effect on brand image and brand image has a significant positive effect on purchasing decisions, price perceptions affect purchasing decisions, promotions affect purchasing decisions and product quality affects purchasing decisions